Application of successful marketing Strategies: New Business Setup - Arshi Naim (European Science Publishing, 2023)
There are many reasons for the failure of businesses within two years of span or even less sometimes. One of the reasons is poor audience targeting. Many startups believe that their product or services is for everyone, leading to bland branding, weak marketing communications and low conversion rates. As a startup, one has to clearly identify the real target market. The product and services should fit for the same target market specifically. Also it is important to define target market correctly because it’s a general term and is used to describe the people who will use the product or series. Therefore clear visualization of the target market and audience should be defined for the specific product and services. As a suggestion to this problem, these researches provide a simple solution by defining the marketing strategies and explaining the methods of market segmentation.
Keywords: Marketing, Business, Marketing Strategies, etc.